Structural Characterization of Phosducin and Its Complex with the 14-3-3 Protein - Kacirova, Miroslava; Kosek, Dalibor; Kadek, Alan; Man, Petr; Vecer, Jaroslav; Herman, Petr; Obsilova, Veronika; Obsil, Tomas (The Journal of biological chemistry, 2015)
Phosducin (Pdc), a highly conserved phosphoprotein involved in the regulation of retinal phototransduction cascade, transcriptional control, and modulation of blood pressure, is controlled in a phosphorylation-dependent manner, including the binding to the 14-3-3 protein. However, the molecular mechanism of this regulation is largely unknown. Here, the solution structure of Pdc and its interaction with the 14-3-3 protein were investigated using small angle x-ray scattering, time-resolved fluorescence spectroscopy, and hydrogen-deuterium exchange coupled to mass spectrometry. The 14-3-3 protein dimer interacts with Pdc using surfaces both inside and outside its central channel. The N-terminal domain of Pdc, where both phosphorylation sites and the 14-3-3-binding motifs are located, is an intrinsically disordered protein that reduces its flexibility in several regions without undergoing dramatic disorder-to-order transition upon binding to 14-3-3. Our data also indicate that the C-terminal domain of Pdc interacts with the outside surface of the 14-3-3 dimer through the region involved in Gtβγ binding. In conclusion, we show that the 14-3-3 protein interacts with and sterically occludes both the N- and C-terminal Gtβγ binding interfaces of phosphorylated Pdc, thus providing a mechanistic explanation for the 14-3-3-dependent inhibition of Pdc function.
Keywords: 14-3-3 Proteins; Animals; proteiny 14-3-3; fosfoproteiny; Binding Sites; Protein Structure, Tertiary; vazebná místa; sekvence aminokyselin; vazba proteinů; terciární struktura proteinů; lidé; Phosphoproteins; Amino Acid Sequence; Eye Proteins; proteiny vázající GTP - regulátory; Models, Molecular; oční proteiny; molekulární modely; fosforylace; krysa rodu Rattus; zvířata; Protein Binding; Rats; Phosphorylation; GTP-Binding Protein Regulators; Humans